The reality of using e-learning at the Middle East University - Al-Momani, Taghreed Mousa; AL-Dlalah, Moham'd Mahmod (Opción, 2019)
This research aimed at discovering the reality of using e-learning at the Middle East University (MEU) from its faculty members’ point of view. The descriptive methodology was used. The population consisted of all faculty members at the (MEU) for the second semester of the university year (2018/2019). The results showed that the reality of using e-learning at the (MEU) was medium and there were no significant differences attributed to academic level and sex variables. In conclusion, there is equality and similarity among the faculty members of the Middle East University regarding the use of e-learning.